2007
DOI: 10.1253/circj.71.862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Early Administration of Heparin in Patients With ST-Elevation Myocardial Infarction Treated by Primary Angioplasty

Abstract: Background The effect of adjunctive heparin for primary angioplasty in patients with ST-elevation myocardial infarction (STEMI) is not well established, so the authors investigated the effect of early heparin administration in the emergency room (ER) on initial patency of the infarct-related artery (IRA) and on the clinical outcome in STEMI patients. Methods and Results One hundred and twenty consecutive patients who presented with STEMI less than 12 h from pain onset and who were eligible for primary percutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
(29 reference statements)
3
8
3
Order By: Relevance
“…A subsequent observational study, published two years later by the same Dutch group, showed pre-hospital UFH (≥ 5000 UI) was associated with higher IRA patency than when it was administered upon arrival to the PPCI-capable centre [15]. These latter findings have been supported by two additional international studies [16,17] and by our real-life cohort. In the present study, better TIMI flow grade 2-3 was observed in the pre-transfer group patients that received UFH early.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A subsequent observational study, published two years later by the same Dutch group, showed pre-hospital UFH (≥ 5000 UI) was associated with higher IRA patency than when it was administered upon arrival to the PPCI-capable centre [15]. These latter findings have been supported by two additional international studies [16,17] and by our real-life cohort. In the present study, better TIMI flow grade 2-3 was observed in the pre-transfer group patients that received UFH early.…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, better TIMI flow grade 2-3 was observed in the pre-transfer group patients that received UFH early. Of note, all patients received the same dose of UFH (5000 UI) before transfer, providing a homogeneous sample for suitable comparisons, as opposed to other studies whose protocol required that the UFH dosage was adjusted according to body weight [13] or even mixed patients treated either with heparin or enoxaparin (drugs with different pharmacokinetics and half-lives) [16]. Indeed, a standard and fixed dose makes easier the treatment protocol, helps emergency crews and physicians from non-PPCI centres to remember it and administer it fast, while reducing dosage errors.…”
Section: Discussionmentioning
confidence: 99%
“…14 Chung et al, showed that in STEMI patients, early heparin treatment in emergency improve coronary patency. 16 The difference between the findings of this study and other studies can be related to difference in the sample size, risk factors, angiographic characteristics and the time of reaching patients of pain start time to hospital and receiving treatment. For example in this study, heparin receiving patients had more coronary artery that completely affects the treatment and clinical outcomes of patients.…”
Section: Vd 2--3 Vdcontrasting
confidence: 78%
“…In fact, this study expresses that in STEMI patients, early heparin treatment in emergency leads to improvement coronary patency. 16 It is observed in this study that in case group in comparison to control group the rate of hematoma was higher (3.1% versus zero %) but not meaningful. The incidence rate of hematoma in different studies has been reported for different heparin receivers.…”
Section: Vd 2--3 Vdcontrasting
confidence: 50%
“…Other authors have shown that early use of heparin resulted in improved initial TIMI flow grade, angiographic thrombus burden and rate of slow-flow during the primary angioplasty procedure. 36 But, as in the present study, the use of heparin did not reduce the rate of in-hospital adverse cardiac events. In addition, women, older patients and patients with body mass index <25 had a higher risk of being over-anticoagulated during treatment with heparin.…”
Section: Discussionsupporting
confidence: 45%